Diagnostics of the innovative project implementation using fuzzy network hierarchical models - O. V. Bulygina; J. V. Selyavsky; A. V. Oficerov (Путеводитель предпринимателя)
In this article the features of innovation management are described, the necessity ofdata mining techniques applying for diagnosing the efficiency of complex innovative project is well founded, an iterative procedure for analyzing the effectiveness of project stage implementation using fuzzy hierarchical network models is developed.